2014
DOI: 10.2478/bpasts-2014-0085
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of air-fuel mixture formation in the combustion chambers of the gas engine with two-stage combustion system

Abstract: Abstract.The results of theoretical analysis of a mixture formation process during the compression stroke in a prechamber of the IC (internal combustion) gas engine with the stratified mixtures two-stage combustion system were presented in the paper. The course of excess air-fuel ratio changes in prechamber at ignition time λ kz in function of degree of the mixture condensation during the compression stroke Φ expressing quotient of a temporary cylinder and prechamber volume and maximal value of the volume were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…1B, tions transesterification [4,5]. In the literature it can be found studied on alternative combustion systems such as stratified combustion system which provides the possibility of burning ultra-poor mixture [6][7][8][9]. In recent years great attention is paid to the use of alternative fuels [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…1B, tions transesterification [4,5]. In the literature it can be found studied on alternative combustion systems such as stratified combustion system which provides the possibility of burning ultra-poor mixture [6][7][8][9]. In recent years great attention is paid to the use of alternative fuels [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The search concern for new fuels to power internal combustion engines include not only vehicle traction engines but also stationary engines to power generators, which are built as cogeneration systems to produce electricity and heat . New fuels should reduce the emission of harmful exhaust gases with the constant engine performance and a high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…When burning methane, it is possible to obtain an air excess ratio of 2.5 [4,5], ensuring that the engine work irregularity remains below 5%. The theoretical analysis of the formation of the air-fuel mixture in a gas engine with a two-stage combustion system was carried out by Tutak and Jamrozik [6]. Analyses regarding passive prechambers confirmed that similar values of excess air ratio were obtained in both prechambers [7].…”
Section: Introductionmentioning
confidence: 92%